PENGARUH COMPLETE FEATURES, KEMUDAHAN, DAN KEAMANAN TERHADAP KEPUASAN PENGGUNA ZOOM MEETING PADA MAHASISWA PRODI MANAJEMEN UNIVERSITAS MUHAMMADIYAH PONOROGO - Fitriya Ramadayani; Siti Chamidah; Dwi Warni Wahyuningsih (Gapenas Publisher, 2022)
The research sample was 72 respondents taken from the number of students in the management study program. The results of the study concluded that there was a significant effect on feature completeness on user satisfaction, no significant effect of convenience on user satisfaction, no significant effect on location on user satisfaction and there was a joint effect on feature completeness, convenience and security on user satisfaction zoom encounter . The use of zoom meetings for students of the management study program at the Muhammadiyah University of Ponorogo. Complete features have an influence on user satisfaction, therefore it is recommended that company owners pay attention to features, convenience and security in the Zoom meeting application. The company's results show that there are other factors that can satisfy users besides complete features, convenience and security, therefore it is recommended that companies pay attention to user complaints related to user satisfaction with complete features, convenience and security and can make strategies to improve performance as desired. consumers as meeting zoom users